Recruiting abroad: The role of foreign affinity and labour market scarcity - Mario Bossler (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
I study the recruiting behaviour of German establishments with regard to the use of foreign labour markets. Applying instrumental variable strategies, I find foreign affinity and labour market scarcity to stimulate the use of foreign markets. Regional labour market scarcity is particularly relevant to small firms, and the effect of foreign affinity is largely driven by the share of foreigners in leading positions in large establishments. The results indicate that shortages are functional and foster the use of foreign labour markets, but the large effect of foreign affinity also reveals that the potential of immigrant workers is used selectively.
Keywords: F22; J23; J61; M51; 330; Recruiting; Immigrant workers; Scarcity